GENERAL ACTIVITIES OF OPPOSING AND PROTECTING AGAINST SECURITY THREATS (Security Dialogues, 2024)
Security, as one of the fundamental values of social functioning and a keysubjective feeling of individuals within a society, is often the target of various attacks.The feeling of insecurity can lead to the internal erosion of society and constant demandsto the relevant social control authorities to elevate security measures. However, overlyconspicuous actions and clearly visible measures can also undermine the feeling of security,causing people to feel unsafe due to the omnipresence of high-tech cameras, notifications,and law enforcement presence. This may indicateto individuals that something is “not right.”The authors of this paper have presented specific preventive-repressive steps and measuresin the field of protection against threats. The primary requirement of the security system isdeterrence from attacks, which is the aim of preventive measures discussed in this paper.By integrating all forms and types of protection, the degree of threat is reduced, and thelevel of security is increased. Therefore, this paper presents elements of preventive reaction,with a projection of integrating all subjects in preventing and eliminating security threatsin terms of maintaining everyday habitual activities. All the aforementioned is accompaniedby a discussion with arguments for and against certain measures, potential encroachmentson human rights, and the paper concludes with considerations and proposals for the mosteffective actions.
Keywords: threats, security, measures, projects, protection